2016
DOI: 10.1016/j.neuropsychologia.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired acquisition of new words after left temporal lobectomy despite normal fast-mapping behavior

Abstract: Word learning under different conditions has been proposed to rely on different brain regions including the temporal lobes, and the left temporal lobe appears to be especially important. In order to investigate the role of the left temporal lobe in word learning under different conditions, we tested whether patients with left temporal lobectomies (N=6) could learn novel words using two distinct learning formats. Previous research has shown that word learning in contrastive fast mapping conditions may rely on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
(123 reference statements)
2
24
0
Order By: Relevance
“…Inconsistent with findings from Sharon et al (2011) and contrary to our hypothesis, our results showed no significant benefit in the FM condition for the DS group. This result is consistent with other recent work failing to measure a FM benefit in healthy older adults, memory-impaired patients (damage to the hippocampus), patients with amnesia (damage to the hippocampus), and patients with left temporal lobectomies (Greve et al, 2014; Smith et al., 2014; Warren & Duff, 2014; Warren et al, 2016). Therefore, given these recent findings, there is mixed evidence regarding the benefit of FM for the retention of arbitrary labels in individuals that do not have amnesia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Inconsistent with findings from Sharon et al (2011) and contrary to our hypothesis, our results showed no significant benefit in the FM condition for the DS group. This result is consistent with other recent work failing to measure a FM benefit in healthy older adults, memory-impaired patients (damage to the hippocampus), patients with amnesia (damage to the hippocampus), and patients with left temporal lobectomies (Greve et al, 2014; Smith et al., 2014; Warren & Duff, 2014; Warren et al, 2016). Therefore, given these recent findings, there is mixed evidence regarding the benefit of FM for the retention of arbitrary labels in individuals that do not have amnesia.…”
Section: Discussionsupporting
confidence: 92%
“…Much work has been conducted regarding the role of sleep in this process (Diekelmann & Born, 2010). However, a few studies investigating a learning mechanism called fast mapping (FM), have provided some evidence suggesting that the rapid acquisition of novel arbitrary associations can be achieved independently of the hippocampus when words are learned under certain conditions (Sharon, Moscovitch, & Gilboa, 2011, but also see Greve, Cooper, & Henson, 2014; Smith, Urgolites, Hopkins, & Squire, 2014; Warren & Duff, 2014; Warren, Tranel, & Duff, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…We speculate that non-hippocampal brain regions or structures that contribute to statistical learning may include medial temporal lobe neocortex (McClelland et al, 1995;Norman and O'Reilly, 2003) and basal ganglia (Poldrack et al, 2001;Poldrack and Packard, 2003;Poldrack and Rodriguez, 2004) among others (Bischoff-Grethe et al, 2000;McNealy et al, 2006;Turk-Browne et al, 2009;Karuza et al, 2013). CSSL may also benefit more specifically from contributions by a network of language-related brain regions including anterior and lateral temporal lobes (McNealy et al, 2006;Davis et al, 2009;Karuza et al, 2013;Warren et al, 2016). Additional functional neuroimaging and neuropsychological investigations might address this hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…The role of anterior and medial temporal lobe structures in learning by means of fast mapping 4 Despite evidence that FM can enable direct integration of arbitrary associations, other studies revealed contradictory findings (cf. Cooper, Greve, & Henson, 2019;Greve, Cooper, & Henson, 2014;Smith, Urgolites, Hopkins, & Squire, 2014;Warren & Duff, 2014;Warren, Tranel, & Duff, 2016). However, the experimental designs and procedures of some of these studies deviated from the original paradigm, such that learning was intentional (e.g., Warren & Duff, 2014) or the associations had been repeatedly recalled before the recognition memory test (e.g., Warren & Duff, 2014;Warren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cooper, Greve, & Henson, 2019;Greve, Cooper, & Henson, 2014;Smith, Urgolites, Hopkins, & Squire, 2014;Warren & Duff, 2014;Warren, Tranel, & Duff, 2016). However, the experimental designs and procedures of some of these studies deviated from the original paradigm, such that learning was intentional (e.g., Warren & Duff, 2014) or the associations had been repeatedly recalled before the recognition memory test (e.g., Warren & Duff, 2014;Warren et al, 2016). Moreover, rapid cortical integration through FM was not always investigated in patients with lesions confined to the hippocampus but also in patients with extended lesions to extra-hippocampal structures or with complete left-temporal lobectomies (Warren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%